Model of Civil Service Career Development at the Ministry of Home Affairs at the West Nusa Tenggara IPDN Campus - Fanila Kasmita Kusuma; Rudy Handoko; Arif Darmawan (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Increasing an employee's career will not happen by itself because the success of an employee's career requires planning and development in its implementation. The purpose of this study is to describe the pattern of career development and to analyze the effectiveness of career development as well as to develop an ideal model for the career development of state civil servants (ASN). This descriptive qualitative research uses a case study approach at the Institute of Domestic Education (IPDN) on the West Nusa Tenggara Campus, and data is taken from interviews with echelon 1 to echelon 4 officials as well as expert staff outside the government. The analysis was carried out interpretively on the data that had been categorized according to the themes compiled. Law No. 5 of 2014 concerning State Civil Apparatus stipulates that Government Agencies are required to provide integrated Education and Training for Prospective Civil Servants (CPNS) for one (one) year probationary period. In addition, career development for PNS West Nusa Tenggara Provincial Government is focused on aspects of PNS planning, recruitment, selection, placement, coaching and career systems, performance management systems, education and training systems, competency standards, empowerment, and civil servant codes of ethics.